3-O-Laurylglyceryl ascorbate activates the intracellular antioxidant system through the contribution of PPAR-γ and Nrf2. Issue 3 (June 2016) - Katsuyama, Yushi; Tsuboi, Tatsuya; Taira, Norihisa; Yoshioka, Masato; Masaki, Hitoshi
Highlights: We synthesized 3- O -laurylglyceryl ascorbate (VC-3LG) as an ascorbic acid derivative. VC-3LG elicited a superior reduction of intracellular ROS with extracellular stimuli. VC-3LG activated the anti-oxidative system through activation of PPAR-γ and Nrf2. Abstract: Background: Ascorbic acid (AsA) has multifunctional effects on physiology and aging including the prevention and improvement of skin pigmentation and wrinkles. AsA has scavenging effects against various types of reactive oxygen species (ROS), which are initiators of aging and premature aging of the skin. However, AsA not only has a quite unstable characteristic, but also has low skin penetration. In addition, existing water-soluble AsA derivatives are not effective to improve its penetration of the skin. Objective: To investigate the antioxidant effect of a newly synthesized amphipathic derivative of AsA, 3- O -laurylglyceryl ascorbate (VC-3LG), in which a laurylglyceryl group was introduced into AsA. Methods: Intracellular ROS levels in keratinocytes were evaluated using the 2′, 7′-Dichlorofluorescein diacetate (DCFHDA) assay. Real-time PCR was used to investigate the mechanism of the antioxidant effect of VC-3LG. Results: Although VC-3LG had less ability to scavenge ROS compared to AsA, it elicited a superior reduction of intracellular ROS levels, with or without extracellular stimuli such as exposure to H2 O2 or UVB. The results show that VC-3LG up-regulates the expression of mRNAs encoding peroxisome proliferator activated receptor-γ (PPAR-γ) and nuclear factor E2-related factor 2 (Nrf2), which in turn up-regulate the levels of mRNAs encoding γ-glutamyl cysteine synthase (γ-GCS), heme oxygenase-1 (HO-1) and NAD(P)H quinone oxidoreductase-1 (NQO1). Furthermore, the Nrf2 mRNA level is down-regulated in siPPAR-γ treated cells, and the effects of VC-3LG on PPAR-γ and Nrf2 mRNA levels are reduced by PPAR-γ knockdown. Conclusion: Taken together, we conclude that VC-3LG has an antioxidant effect and scavenges ROS directly as well as stimulating intracellular antioxidants such as GSH through the PPAR-γ and Nrf2 signaling pathway.